Development of compact heat exchanger with additive manufacturing (Evaluation of condensation thermal-hydraulic characteristics of block type compact heat exchanger) - Kota CHIBA; Chikako IWAKI; Masayuki SATO; Yoshinori KATAYAMA; Katsunori SHIIHARA; Shota ARAKI; Hideshi NAKANO; Tooru TANAKA (Nihon Kikai Gakkai ronbunshu)
Heat exchangers are used in a wide range of applications and there has been a great deal of research and development on improving their performance, but in recent years there has been a growing demand for miniaturization, especially in energy systems. In the development of a compact heat exchanger with additive manufacturing, the thermal-hydraulic characteristics of a block type heat exchanger were experimentally evaluated. Three types of block type heat exchangers with different internal channel structures were manufactured by using powder bed fusion type metal 3D printer. In the tests, condensation heat exchange tests with cooling water and steam and single-phase heat exchange tests with cooling water and hot water were conducted. As a result, it was confirmed that the heat exchange rate could be improved by staggered arrangement of the channels and by reducing the diameter of the channels. In the condensation heat transfer test, the amount of heat exchange was the same regardless of the amount of cooling water. This is because the steam is fully condensed under all test conditions and condensation heat transfer is dominant. However, the distance at which steam condenses completely is reduced by arranging the channels in a staggered pattern and reducing the channel diameter. From these facts, the heat exchange rate can be further increased by increasing the steam flow rate. It has been confirmed that Shah's equation (Shah, 2022) can predict the results of condensation heat exchange tests with an accuracy of ±10%. In addition, the pressure drop was 0.5~2.0 kPa, indicating that the block heat exchanger has a high heat exchange performance but small pressure drop.